LncRNA XIST regulates atherosclerosis progression in ox-LDL-induced HUVECs - Gao Hongmei (De Gruyter, 2021)
Long noncoding RNAs (lncRNAs) have been verified as vital regulators in human disease, including atherosclerosis. However, the precise role of X-inactive-specific transcript (XIST) in atherosclerosis remains unclear. The proliferation and apoptosis of human umbilical vein endothelial cells (HUVECs) exposed to low-density lipoprotein (ox-LDL) were assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazol-3-ium bromide, and flow cytometry assays, correspondingly. The western blot assay was used to quantify protein expression. Lactate dehydrogenase activity and the concentrations of inflammatory factors were measured by matched kits. The real-time quantitative polymerase chain reaction (qPCR) was used to determine α-smooth muscle actin, smooth muscle protein 22-α, XIST, miR-98-5p, and pregnancy-associated plasma protein A (PAPPA) levels in HUVECs. The relationship among XIST, miR-98-5p, and PAPPA was analyzed by dual-luciferase reporter, RNA immunoprecipitation, and RNA pull-down assays. We found ox-LDL repressed proliferation and induced inflammation and apoptosis in HUVECs. Loss-of-functional experiment suggested that the downregulation of XIST overturned the ox-LDL-induced effects on HUVECs. Additionally, overexpression of miR-98-5p-induced effects on ox-LDL-stimulated HUVECs was abolished by upregulation of XIST. However, silencing of miR-98-5p strengthened the ox-LDL-induced effects on HUVECs by increasing expression of PAPPA. Mechanistically, XIST could regulate PAPPA expression in ox-LDL-induced HUVECs by sponging miR-98-5p, providing understanding for atherosclerosis.